Explaining religion without explaining it away : trust, truth, and the evolution of cooperation in Roy A. Rappaport´s "the obvious aspects of ritual". - Watanabe, John M. (American Antropological Association, 1999)
Moving beyond the ecological functionalism of Pigs for the Ancestors, Roy Rappaport's subsequent work on ritual explored how the Òobvious aspectsÓ of ritual's formalism and the need to perform it literally embody in its performers expressions of sanctity and truth that counter the threats of lying and alternative inherent in symbolic communication. He recognized that symbolic meaning and truth presuppose social cooperation and trust between individuals, and ritual serves uniquely to reaffirm this mutuality at the level of both individual behavior and conventional meaning. Through a study of male greetings among olive baboons (Papio cynocephalus anubis), this paper illustrates how ritual in Rappaport's sense may indeed intensify cooperation in socially complex but nonlinguistic contexts by establishing a behaviorally transparent means of certifying otherwise opaque individual intentions. Thus, not only may ritual sanctify symbolic communication, but it also may have played a crucial role in its evolution